THE GREENWASHING PHENOMENON IN MARKETING COMMUNICATIONS AND ITS IMPACT ON CONSUMER CYNICISM - Iing Saefudin (FEBI UIN Sunan Gunung Djati Bandung, 2025)
Rising environmental awareness has fueled a surge in green marketing campaigns. Unfortunately, corporations often exploit this opportunity to engage in greenwashing, a misleading marketing communication practice involving sustainability claims. This study aims to examine the phenomenon of greenwashing in depth and analyze its impact on consumer cynicism. Using qualitative methods with a literature review approach, this study collected and analyzed various academic sources, journals, and related documents. The results show that greenwashing tactics manifested through vague claims, the exploitation of visual elements, and the concealment of ecological facts constitute a failure of communication ethics that triggers severe cognitive dissonance in consumers. The accumulation of this sense of betrayal crystallizes into chronic consumer cynicism, a form of deep distrust of the social motives of all corporations. The destructive impact of this cynicism creates a domino effect that undermines the entire green market ecosystem, as consumers tend to generalize and reject honest claims from truly sustainable companies. These findings underscore the importance of implementing radical transparency by corporations and the urgency of strict legal regulatory intervention by governments to break the chain of market distrust.